Penentuan Kualitas Air untuk Perkembangan Ikan Lele Sangkuriang Menggunakan Metode Fuzzy SAW - Dony M Sihotang (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
The purpose of this paper is to implement Fuzzy Simple Additive Weighting (F-SAW) method in determination of water quality for the development of Sangkuriang catfish, using six criteria, i.e. temperature, pH, DO, brightness, plankton, and odor, using 15 alternatives (pool). There are two test scenarios that have been done in this research to obtain system accuracy level, which are: 1) result of system compared with assessment from an expert; and 2) the results of the system compared with assumption of the study that the alternative with the best data should be ranked first and the alternative with the worst data should be rated last. The results obtained from the first scenario shows the level of accuracy is 87%, while the results obtained from the second scenario shows 100% accuracy rate.